LEGAL ANALYSIS OF BROADCASTING ETHICS ON FTV SUARA HATI WIFE IN INDOSIAR - Annisa, Annisa; Uyun, Zafirah Quroatun (KINEMA: Jurnal Komunikasi dan Penyiaran, 2024)
The main problem in this thesis is the wedding procession that is not shown in the FTV Suara Hati Istri episode "How Can I Make My Husband Not Bored of Me" which is contrary to the religion being played. The purpose of this discussion is to analyze the semiotics contained in the FTV which is then reviewed from the broadcasting ethics law to see whether there is a violation or not. This type of research is analysis of media texts that use a focus on content analysis with a qualitative approach. Roland Barthes' semiotic analysis method is used to analyze signs and how they work by paying attention to the system of denotations, connotations and myths contained in scenes that are related to the FTV wedding procession. Guaranteeing the validity of the data in this study is an extension of observations and increases persistence. The results of this study indicate that the denotative meaning in the TV movie differs from the connotative meaning as evident from the portrayal and arrangement of characters, leading to violations of broadcasting ethics law. Furthermore, the connotative meaning contradicts myths associated with religious values and societal norms, resulting in violations of broadcasting ethics law, specifically under Article 36 Paragraph (1) of Law No. 32 of 2002 concerning Broadcasting, and Article 19 Paragraph (1) of the Indonesian Broadcasting Commission (KPI) Regulation No. 02/P/KPI/03/2012 concerning Broadcast Program Standards (SPS).